Stability of SPEEK-triaminopyrimide polymer electrolyte membrane for direct methanol fuel cell application - Juhana Jaafar; Ismail, A.F.; Matsuura, T.; Mohd Norddin, M.N.A. (Universiti Kebangsaan Malaysia, 2013)
Modification of sulfonated poly (ether ether ketone) (SPEEK) membrane was conducted by incorporating Cloisite 15A® clay and 2,4,6-triaminopyrimidine (TAP) via solution intercalation method. The effect of the Closite and TAP introduction was evaluated in terms of the membrane’s physicochemical and hydration properties. The membrane’s properties were compared among the SPEEK based membranes, including parent SPEEK, SPEEK/Cloisite and SPEEK/Cloisite 15A®/TAP. The uniform dispersion of Cloisite 15A® particles in SPEEK polymer matrices was confirmed by SEM analysis. The stability in water; in terms of dimensional change and dissolution, of the modified membrane was investigated and compared to the parent SPEEK membrane. SPEEK/Cloisite 15A®/TAP nanocomposite membrane exhibited the highest selectivity by means of the ratio of proton conductivity to methanol permeability. Owing to its higher proton conductivity and significantly lower methanol permeabilities and high stability in water environment, SPEEK/Cloisite 15A®/TAP nanocomposite membrane was found to be a potential alternative polymer electrolyte membrane for DMFC applications.